LAMA2-related congenital muscular dystrophy complicated by West syndrome. (March 2015) - Camacho, Ana; Núñez, Noemí; Dekomien, Gabriele; Hernández-Laín, Aurelio; de Aragón, Ana Martínez; Simón, Rogelio
Abstract Background Mutations in the LAMA2 gene cause autosomal recessive laminin α2 related congenital muscular dystrophy. In patients with partial laminin α2 deficiency the phenotype is usually milder than in those with absent protein. Apart from the typical white matter abnormalities, there is an increased risk of cerebral complications such as epilepsy and mental retardation, despite a structurally normal brain. Methods/results We present a patient with primary partial laminin α2 deficiency due to a homozygous novel LAMA2 missense mutation who developed West syndrome in his first year of life. To our knowledge, this combination has not previously been reported. A 5 year-old boy exhibited global hypotonia with generalized muscle weakness from birth. At 8 months of age he presented infantile spasms and an EEG finding of hypsarrhythmia. Seizures were controlled in a few weeks with intramuscular synthetic ACTH, followed by valproic acid. Two years later antiepileptic medication was withdrawn. He achieved unsupported walking at the age of 4, but his cognitive status corresponded to a 2 year-old child. Epilepsy has not recurred and brain MRI showed the typical white matter abnormalities without associated neuronal migration defects. Conclusion This report widens the clinical spectrum of cerebral manifestations related with mutations in LAMA2. The beginning of a severe epileptic encephalopathy modifies the natural history of the disease.